Reduced Blood Flow in Normal White Matter Predicts Development of Leukoaraiosis. Issue 10 (October 2015) - Bernbaum, Manya; Menon, Bijoy K; Fick, Gordon; Smith, Eric E; Goyal, Mayank; Frayne, Richard; Coutts, Shelagh B
The purpose of this study was to investigate whether low cerebral blood flow (CBF) is associated with subsequent development of white matter hyperintensities (WMH). Patients were included from a longitudinal magnetic resonance (MR) imaging study of minor stroke/transient ischemic attack patients. Images were co-registered and new WMH at 18 months were identified by comparing follow-up imaging with baseline fluid-attenuated inversion recovery (FLAIR). Regions-of-interest (ROIs) were placed on FLAIR images in one of three categories: (1) WMH seen at both baseline and follow-up imaging, (2) new WMH seen only on follow-up imaging, and (3) regions of normal-appearing white matter at both time points. Registered CBF maps at baseline were used to measure CBF in the ROIs. A multivariable model was developed using mixed-effects logistic regression to determine the effect of baseline CBF on the development on new WMH. Forty patients were included. Mean age was 61 ± 11 years, 30% were female. Low baseline CBF, female sex, and presence of diabetes were independently associated with the presence of new WMH on follow-up imaging. The odds of having new WMH on follow-up imaging reduces by 0.61 (95% confidence interval = 0.57 to 0.65) for each 1 mL/100 g per minute increase in baseline CBF. We conclude that regions of white matter with low CBF develop new WMH on follow-up imaging.